The role of Th17 cells in inflammatory bowel disease and the research progress - Chen, Lu; Ruan, Guangcong; Cheng, Yi; Yi, Ailin; Chen, Dongfeng; Wei, Yanling (Frontiers in Immunology, 2023)
Th17 cells play an important role in the abnormal immune response of inflammatory bowel disease (IBD) and are involved in the development and progression of inflammation and fibrosis. Th17-cell differentiation is regulated by cytokines and intestinal bacteria, and regulates the intestinal mucosal immune microenvironment by secreting cytokines such as IL-17, IL-21, and IL-26, etc. It is worth mentioning that although abnormal expression of Th17 can lead to a variety of autoimmune diseases, including IBD. In existing reports, various biologics have different effects in targeting Th17 cells in the treatment of Crohn's disease (CD). In addition, expanding data indicated that gut microbes are important regulators of Th17 cellular immunity. To further understand the role of Th17 cells in the progression of IBD and their therapeutic potential, we will review the progress of related research on Th17 cells in IBD, and focus on the immune regulation between Th17 cells and gut microbiota.